The Roles of Glycodelin in Cancer Development and Progression - Cui, Juan; Liu, Yanguo; Wang, Xiuwen (Frontiers in Immunology, 2017)
Glycodelin is a kind of glycoprotein expressed in secretory endometrium, pregnancy deciduas, and amniotic fluid originally, which is vital for the maintenance of normal human reproductive activities. Recent researches have reported that glycodelin is specifically expressed in various malignancies, including female-specific cancers such as endometrial cancer, ovarian cancer and breast cancer, and non-gender specific cancers including lung cancer, and colon cancer, and glycodelin expression correlates with the diagnosis and prognosis of cancer patients. This review focuses on the expression of glycodelin in different cancers and its role in cancer development and progression. Glycodelin possesses the abilities to regulate cancer cell proliferation, differentiation, and invasion, promote cancer angiogenesis, and modulate the differentiation and function of immune cells including T cells, dendritic cells, monocyte-macrophages, natural killer cells and B cells participating in cancer development. The expression of glycodelin can be regulated by stromal cells, lysophosphatidic acid, histone deacetylase inhibitors, and relaxin. In summary, glycodelin is a promising biomarker for the diagnosis and prognosis of cancer patients, and depending on its distinct immunoregulatory effects, glycodelin can be a prospective target for cancer immunotherapy.